2023
DOI: 10.3390/antibiotics12020274
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Recent Alternatives to Antibiotics for the Control of Bacterial Pathogens with an Emphasis on Foodborne Pathogens

Abstract: Antimicrobial resistance (AMR) is one of the most important global public health problems. The imprudent use of antibiotics in humans and animals has resulted in the emergence of antibiotic-resistant bacteria. The dissemination of these strains and their resistant determinants could endanger antibiotic efficacy. Therefore, there is an urgent need to identify and develop novel strategies to combat antibiotic resistance. This review provides insights into the evolution and the mechanisms of AMR. Additionally, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 467 publications
0
17
0
Order By: Relevance
“…Numerous bacteriocins, which affect both Gram-positive and Gram-negative bacteria, are produced by commensal bacteria and include organic acids like lactic, propionic, and butyric microbes. In vitro experiments have demonstrated the inhibitory effects of reuterin , a bacteriocin generated by Lactobacilli , on Salmonella, Shigella, Clostridium , and Listeria ( Wickramasuriya et al, 2022 ; Beldowska et al, 2023 ; Helmy et al, 2023 ). Short-chain fatty acids (SCFA) and hydrogen peroxide are additional substances commensal microorganisms generate.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous bacteriocins, which affect both Gram-positive and Gram-negative bacteria, are produced by commensal bacteria and include organic acids like lactic, propionic, and butyric microbes. In vitro experiments have demonstrated the inhibitory effects of reuterin , a bacteriocin generated by Lactobacilli , on Salmonella, Shigella, Clostridium , and Listeria ( Wickramasuriya et al, 2022 ; Beldowska et al, 2023 ; Helmy et al, 2023 ). Short-chain fatty acids (SCFA) and hydrogen peroxide are additional substances commensal microorganisms generate.…”
Section: Discussionmentioning
confidence: 99%
“…Strains that can exhibit the desired effect would be considered for further testing. Detailed steps for the development of probiotics were reviewed previously [ 27 , 28 ]. Furthermore, different culture methods are used involving growing probiotic strains in a laboratory setting using different types of media such as MRS (de Man, Rogosa, and Sharpe) and M17.…”
Section: Identification and Characterization Of New Probiotic Strainsmentioning
confidence: 99%
“…Although large numbers of AMPs have been characterised, a small number have been applied in clinical trials, and a limited number have been approved by the US Food and Drug Administration (FDA) [ 245 ]. Most clinically used AMPs are limited to topical applications due to their systemic toxicity, the susceptibility of the peptides to degradation by proteases, and rapid kidney clearance when administrated orally [ 246 ].…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%
“…Panáček et al [ 292 ] showed that E. coli 013 , P. aeruginosa CCM 3955, and E.coli CCM 3954 can develop resistance to Ag NPs after repeated exposure to increased production of the adhesive flagellum protein flagellin, which stimulates the aggregation of Ag NPs and destruction their antibacterial effect. Additionally, in several studies, toxic effects of the same NPs have been reported [ 245 , 293 ]. For example, Hemeg [ 294 ] showed that Ag NPs can accumulate in human organs like the colon, liver, spleen or bone, causing damage and/or decreased organ efficacy and dysfunction.…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%